Determinants of Non-Performing Loans: Banking Sector Listed in Indonesia Stock Exchange - Jason Stefano; Sofia Prima Dewi (Jurnal Ekonomi, 2022)
This study proposes to obtain empirical evidence whether profitability has a negative effect on non-performing loans, whether income diversification has a positive effect on non-performing loans, whether bank capital has a negative effect on non-performing loans, and whether bank liquidity has a negative effect on non-performing loans. The sample used in this research are 28 banking companies listed on the Indonesia Stock Exchange during the 2017-2019 period. Sampling was carried out using purposive sampling technique and data were processed using Eviews 10 software. The results indicate that profitability has a negative effect on non-performing loans, income diversification has a positive effect on non-performing loans, bank capital has no negative effect on non-performing loans, and bank liquidity has no negative effect on non-performing loans.